Studi Literatur: Uji Kemampuan Konsorsium Isolat Bakteri Selulolitik dalam Mempercepat Dekomposisi Tandan Kosong Kelapa Sawit: Literature Study: Ability Test Of The Consortium of Cellulolitic Bacterial Isolates in Accelerating The Decomposition of Empty Palm Oil Signs - Clara Aprilya Kurniawan; Meri Afriani; Ashri Maulana; Gusmawartati (Jurnal Ilmu Tanah dan Lingkungan, 2021)
One alternative way of managing EFB is composting, beside being able to reduce the volume of waste, composting can increase the nutritional value of EFB. There are several ways to speed up composting process. Biological treatment by growing develop proven microbes (high ability in breaking down materials) which is composted. Bacteria are the most dominant group in the ground. Its small size, prokaryotic and single-celled give advantages in reshuffling organic matter over fungi and groups actinomycetes. The microbes that capable of hydrolyzing cellulose is called cellulolytic microorganisms that have the ability to grow on cellulose and can decompose these cellulose materials. Solving system cellulose into glucose consists of three types of cellulase enzymes, namely endo-ß-1.4-glucanase, exo-ß-1.4-glucanase, and ß-glucosidase. In general, bacteria cellulolytics can not produce these three enzymes, so they need their consortium to make EFB reform more effective and efficient.